1997
DOI: 10.1007/s002130050184
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic acetylcholine receptor (nACh-R) agonist-induced changes in brain monoamine turnover in mice

Abstract: The aim of the present study was to evaluate the effects of nicotinic acetylcholine receptor (nACh-R) agonists such as (-)-nicotine and related compounds on brain monoamine turnover. A single administration of (-)-nicotine (0.04, 0.2, 1.0, and 5.0 mg/kg SC) increased both noradrenaline (NA) and dopamine (DA) turnover in a dose-dependent manner, and the maximum effects were achieved 30 min after treatment with (-)-nicotine (1.0 mg/kg). The effect of (-)-nicotine on serotonin (5-HT) turnover was complicated; 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…However, unlike the IM group, the antidepressant drugs which inhibit the reuptake of monoamines (AT, CL, and FL) were not significantly effective in the NC group in the forced swimming test for these drugs could not be predicted based on the previous data and suggested a contribution of the monoamine system to the depression-related behavioral alterations in both forced swimming and tail suspension tests (Steru et al, 1985;Rénéric et al, 1998;Fujishiro et al, 2001). Nevertheless, considering the characteristic NC--tem in the forced swimming test, which include the alterations in dopamine levels (Tani et al, 1997;Renard et al, 2003), there seems to be a possibility that the antidepressants such as AT, CL and FL, which inhibit mainly the reuptake of noradrenaline and 5-hydroxy-tryptamine (5-HT), cannot antagonize effectively the NC-induced depressive swimming behaviors, at least during the test time, as compared to the other "antidepressant" drugs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, unlike the IM group, the antidepressant drugs which inhibit the reuptake of monoamines (AT, CL, and FL) were not significantly effective in the NC group in the forced swimming test for these drugs could not be predicted based on the previous data and suggested a contribution of the monoamine system to the depression-related behavioral alterations in both forced swimming and tail suspension tests (Steru et al, 1985;Rénéric et al, 1998;Fujishiro et al, 2001). Nevertheless, considering the characteristic NC--tem in the forced swimming test, which include the alterations in dopamine levels (Tani et al, 1997;Renard et al, 2003), there seems to be a possibility that the antidepressants such as AT, CL and FL, which inhibit mainly the reuptake of noradrenaline and 5-hydroxy-tryptamine (5-HT), cannot antagonize effectively the NC-induced depressive swimming behaviors, at least during the test time, as compared to the other "antidepressant" drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Although the detailed neuronal modifications correlated with the NC-suppressed swimming behaviors have not been elucidated, nAChR-mediated alterations in dopamine levels, etc. ), which can be caused characteristically by NC, have been demonstrated (Tani et al, 1997). Furthermore, even without any drug or stressor treatments, behavioral alterations during the forced swimming test, unlike the tail suspension test, have been reported to be accompanied immediately by rapid alterations in the brain monoamine levels (Renard et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The different effects of the three nicotinic agonists may relate to their different effects on dopamine transmission. Studies in vitro and in vivo suggest that common nicotinic mechanisms may be responsible for nicotine-and nornicotine-induced increases in dopamine (Grady et al 1992;Dwoskin et al 1993;Teng et al 1997), but lobeline may be different (Grady et al 1992;Clarke and Reuben 1996;Tani et al 1997). Terry et al (1998) suggested that lobeline might exhibit different receptor subtype selectivity compared with nicotine, or its effects may be via non-nicotinic mechanisms.…”
Section: Discussionmentioning
confidence: 95%
“…2d). However, the effects of these antidepressant drugs were attenuated in the NC and IM-NC groups in the forced swimming test, which seemed to be correlated with the characteristic NC-induced nAChR--ver (Tani et al, 1997). Furthermore, in the forced swimming test, rapid alterations in brain monoamine levels have been reported even without any drug or stressor treatments (Renard et al, 2003), and thus there are postest itself may enhance the neuronal effects of NC and contribute to the attenuated effects of the antidepressant drugs related to monoamine reuptake.…”
Section: Effects Of "Antidepressant" Drugsmentioning
confidence: 89%
“…Although there are several similarities in the neuronal responses (e.g. similar alterations in stress hormones and catecholamines) between the effects of IM and NC (Morse, 1989;Takahashi et al, 1998), the NC-induced characteristic depression-related behavioral and neuronal alterations, which were not observed in the IM treatment, have been reported in animal experimental models: occurrence of antidepressant-like effects at early time points (within 15 min) after repeated NC treatments, which is accompanied by early characteristic alterations in the interactions between nicotinic cholinergic and serotonergic systems (Tizabi et al, 1999;Vázquez-Palacios et al, 2004), and shorter duration (within 24 hr) of the NC-induced depression-like behavioral alterations in the forced swimming test as compared to the IM-induced behaviors, for which nicotinic acetylcholine receptor (nAChR)-mediated, rapid et al ., 1997;Hayase, 2007Hayase, , 2008.…”
Section: Im-and/or Nc-induced Depression-like Behavioral Alterationsmentioning
confidence: 99%